Prospective bladder cancer infrastructure for experimental and observational research on bladder cancer: study protocol for the 'trials within cohorts' study ProBCI - Richters, Anke; Meijer, Richard P; Mehra, Niven; Boormans, Joost L; Nijmegen, Radboud University Medical; van der Heijden, Michiel S; Kiemeney, Lambertus A; Aben, Katja K (BMJ Publishing Group, 2021)
INTRODUCTION: A better understanding of the molecular profile of bladder tumours, the identification of novel therapeutic targets, and introduction of new drugs and has renewed research interest in the field of bladder cancer. We describe the design and setup of a Dutch Prospective Bladder Cancer Infrastructure (ProBCI) as a means to stimulate and accelerate clinically meaningful experimental and observational research. METHODS AND ANALYSIS: ProBCI entails an open cohort of patients with bladder cancer in which the trials within cohorts (TwiCs) design can be embedded. Physicians in participating hospitals prospectively recruit invasive (≥T1) patients with bladder cancer on primary diagnosis for inclusion into the study. Extensive clinical data are collected and updated every 4 months, along with patient-reported outcomes and biomaterials. Informed consent includes participation in TwiCs studies and renewed contact for future studies. Consent for participation in questionnaires and molecular analyses that may yield incidental findings is optional. ETHICS AND DISSEMINATION: The Dutch ProBCI is a unique effort to construct a nation-wide cohort of patients with bladder cancer including clinical data, patient-reported outcomes and biomaterial, to facilitate observational and experimental research. Data and materials are available for other research groups on request through www.probci.nl. Ethics approval was obtained from METC Utrecht (reference: NL70207.041.19). TRIAL REGISTRATION NUMBER: NCT04503577.
Keywords: epidemiology; oncology; urological tumours; General Medicine; Journal Article